A Severe Case of Invasive Rhino-Orbito-Cerebral Mucormycosis in a Patient with Acute T-Cell Leukemia with Successful Outcome: a Case Report and a Literature Review - Davainis, Linas; Vasilevska, Dominyka; Zucenka, Andrius; Davainiene, Birute; Pileckyte, Regina; Griskvevicius, Laimonas (Archives of Clinical and Medical Case Reports, 2023)
Mucormycosis is infective disease caused by fungi in order of Mucorales. The fungi invade blood vessels wall, causing infarction and necrosis that are difficult to be reached by antifungal agents, resulting in challenging treatment. Mucormycosis usually occurs in severelly immunosupresed patient, complicating treatment of hematological malignancies and increasing mortality, despite successful treatment of the oncological disease. Mucormycosis carries very high mortality rate (50-85%), some forms, like rhino-orbito-cerebral, and determines over 95% mortality. This manuscript presents a severe case of invasive rhino-orbito-cerebral mucormycosis in a patient after chemotherapy for acute T-cell leukemia with successful outcome after treatment with extensive surgical debridement concomitant with liposomal amphotericin B (LAmB) and isavuconazole, while simultaneously reducing immunosuppression. Despite successful outcome of mucormycosis and sustained leukemia remission rapid spread the invasive fungal infection led to permanent blindness.